Aids in physics: Design and development - Hasim, Norfaridatul Akmar Bt; Karim, Mohd Mustamam Bin Abd; Rahman, Nurulhuda Binti Abd (Universitas PGRI Kanjuruhan Malang, 2020)
Electricity is found to be a difficult topic to learn due to its abstract concepts. Research showed that games based learning using dioramas can help students to interest and enhance students’ understanding in learning abstract Physics topics. As a result, PhyKER Games was developed in order to assist students in the learning of the Electricity circuit topic. ADDIE model (analysis, design, development, implementation and evaluation) as instructional design and develope of PhyKER Games. Dioramas were added in PhyKER Games to depict real scenes. The information delivery and the flow of content follow the ADDIE phases theory. It is hoped that the PhyKER Games would be able to assist students in the learning of Electricity circuit terms of concept understanding and motivation level.